Wybrane koncepcje architektoniczno-wystawiennicze pawilonów narodowych krajów Europy Wschodniej na targach World Expo 2000-2020 w kontekście kreacji wizerunku narodowego - Bizio, Krzysztof (Przegląd Wschodnioeuropejski, 2023)
This article examines the architectural and exhibition concepts of the national pavilions of Lithuania, Latvia, Estonia, Belarus and Ukraine, which were created for the purposes of the World Expo exhibitions in the years 2000-2020 in the context of the promoted national image. After 1991 and the collapse of the USSR, the countries of Eastern Europe began the process of creating their own national images, in which the World Expo exhibitions became one of the most important platforms for international presentations. The article discusses selected exhibition strategies presented by these countries at six exhibitions: World Expo 2000 in Hanover, World Expo 2005 in Aichi, World Expo 2010 in Shanghai, World Expo 2015 in Milan and World Expo in Dubai 2020. The analysis of solutions was carried out from the perspective of searching for unique forms that distinguish the concepts of individual pavilions. The result of the research was the specification of the tendencies that distinguish pavilions of Eastern European countries from other solutions.